POLYORCHIDISM PRESENTING WITH INGUINAL HERNIA:A CASE REPORT AND A REVIEW OF LITERATURE - Muhammad Abid Owais (Baqai Journal of Health Sciences)
Triorchidism is the commonest variety of polyorchidism, an entity with more than two testes is an extremely rare congenital anomaly of the testis. Although removal of the supernumerary testis is a safer alternative proposed, recent literature recommends more conservative approach in normal testes with vigilant regular follow up to screen for malignancy. This case presented as a left inguinal swelling diagnosed as indirect left inguinal hernia with left undescended testis. Intraoperatively indirect inguinal hernia was noted with supernumerary testis at deep ring in addition to normal left testis in hernia sac in the inguinal canal. The ectopic testis was small (2×2×1 cm) lacking epididymis and with short vas deferens. After performing herniotomy and orchidopexdy, supernumerary testis was excised for a possible malignancy. Histopathologicalexamination showed presence of immature testicular tissue.